PERANCANGAN SISTEM PENGENALAN NADA ANGKLUNG MENGGUNAKAN DISCRETE FOURIER TRANSFORM - Sindhi Pradnya Nareswari; Lusiana Haryanti; Muhammad Fathoni Hervi Hermawan; Apri Junaidi (Jurnal Ilmiah Teknologi Infomasi Terapan, 2018)
Angklung is one of Indonesia's traditional musical instruments that has become famous. This popularity certainly invites a lot of people's interest to learn angklung instruments. Online learning are one of the learning technique that is popular to be used. The problem is, not all people who use this learning technique understand the tone that is used in the video. Therefore, this study will create a breakthrough that can help these problems. The result wich is expected is this design can help people recognize tones and improve their skills in music